Engineering Zymomonas mobilis for Robust Cellulosic Ethanol Production. Issue 9 (September 2019) - Xia, Juan; Yang, Yongfu; Liu, Chen-Guang; Yang, Shihui; Bai, Feng-Wu
Abstract : Great effort has been devoted to engineering Saccharomyces cerevisiae with pentose metabolism through the oxido-reductase pathway for cellulosic ethanol production, but intrinsic cofactor imbalance is observed, which substantially compromises ethanol yield. Zymomonas mobilis not only can be engineered for pentose metabolism through the isomerase pathway without cofactor imbalance but also metabolizes sugar through the Entner–Doudoroff pathway with less ATP and biomass produced for more sugar to be used for ethanol production. Moreover, the availabilities of genome sequence information for multiple Z. mobilis strains and advanced genetics tools have laid a solid foundation for engineering this species, and the self-flocculation of the bacterial cells also presents significant advantages for bioprocess engineering. Here, we highlight some of recent advances in these aspects. Highlights: Zymomonas mobilis metabolizes glucose through the Entner–Doudoroff (ED) pathway, with less ATP generated and biomass accumulated for more ethanol production. The large specific cell surface of Z. mobilis together with the ED pathway facilitates glucose uptake and ethanol fermentation. Its metabolic characteristics and narrow substrate spectrum make Z. mobilis unsuitable for fuel ethanol production from sugar- and starch-based feedstocks, but it would be a good host to be engineered for cellulosic ethanol production. When self-flocculated, Z. mobilis can be immobilized within fermenters for high cell density to improve ethanol productivity. Meanwhile, its tolerance to environmental stresses may be enhanced by this morphological change. Both Z. mobilis ZM4 and its self-flocculating mutant ZM401 can tolerate more than 100 g/L ethanol, which is sufficient for cellulosic ethanol production.